Association between the composite dietary antioxidant index and sarcopenia risk in American adults: a cross-sectional NHANES study - Lingling Zhu; Yun She; Xiangyun Guo; Jinran Qin; Xiqiao Zhou; Jiangyi Yu; Qianhua Yan (BMJ Public Health, 2025)
Background Given the absence of specific pharmacological treatments for sarcopenia, identifying effective lifestyle and dietary interventions is imperative. This study aims to explore the association between the composite dietary antioxidant index (CDAI) and sarcopenia, offering new insights into nutritional strategies for sarcopenia-prone populations.Methods This cross-sectional study analysed secondary data from the National Health and Nutrition Examination Survey cycles spanning 2001–2006 and 2011–2018. Weighted multivariate logistic regression and restricted cubic spline (RCS) analyses were employed to evaluate the non-linear association between CDAI and sarcopenia and to perform stratified analyses.Results In this study, encompassing 19 683 American adults, representative of the national population of 132 140 502 residents, 7.97% were diagnosed with sarcopenia. Across all adjusted models, a higher CDAI was inversely associated with the risk of sarcopenia (OR 0.94, 95% CI 0.92, 0.96; P<0.0001). The highest quartile of CDAI scores to those in the lowest revealed significantly reduced odds of sarcopenia (OR 0.46, 95% CI 0.38, 0.56; P<0.0001). RCS analysis demonstrated a non-linear relationship between CDAI and sarcopenia. Additionally, stratified analyses indicated that the inverse association between CDAI and sarcopenia was more pronounced among participants with higher educational levels and those diagnosed with tumours.Conclusions There was a negative relationship between CDAI scores and the prevalence of sarcopenia, suggesting that higher CDAI scores may help in managing and preventing the occurrence of sarcopenia.